Availability and readability of online patient information on clubfoot: Assessment of paediatric hospital clubfoot web pages. (June 2021) - Xie, Michael; Young, Jason; May, Collin
Abstract: Purpose: To determine the availability and readability of online patient information (OPI) provided by paediatric hospitals in the United States using clubfoot as a model condition Methods: The websites of the top 95 paediatric hospitals identified using US News & World Report were included. The names of paediatric hospitals and the terms "clubfoot", "clubfeet" and "talipes equinovarus" were entered into the Google search engine. Readability was assessed using five validated metrics and the composite grade level (CGL). The number of unpaid monthly visits was calculated with the Ahrefs Organic Traffic Score (OTS) tool. Data for paediatric hospitals were compared with the same metrics for the top ten Google search results. Results: Of 95 paediatric hospitals, 29 (30.5%) did not have at least one web page dedicated to clubfoot. The 128 web pages representing 66 paediatric hospitals had an average CGL of 9.4, representing a readability level requiring some high school education. The mean OTS for all paediatric hospitals was 116 estimated visits per month, which was significantly less than that for the top ten Google clubfoot search results (3035.1; p < 0.0001). Conclusion: Paediatric hospital web pages on clubfoot were visited much less frequently than those from the top ten Google search results. Only two web pages (1.6%) from paediatric hospitals offered OPI on clubfoot that met the American Medical Association recommended reading level (sixth-grade level). Paediatric hospitals should create OPI on clubfoot with appropriate readability and accessibility for patient families. Level of Evidence: N/A